Case reportPrimary angiitis of the central nervous system: 2 atypical cases - Pagni, Fabio; Isimbaldi, Giuseppe; Vergani, Francesco; Casiraghi, Paolo; Marzorati, Laura; Migliorino, Guglielmo; Cattoretti, Giorgio (Folia Neuropathologica, 2012)
The presence of an angiitis process in the central nervous system (CNS) characterizes different groups of conditions: from idiopathic pachymeningitis to lymphoproliferative disorders. In absence of specific infections, inflammatory and neoplastic diseases, the term “PACNS” (Primary Angiitis of the CNS) was proposed to indicate a peculiar vascular inflammation of unknown origin of meningeal vessels extending to the brain or spinal cord parenchyma. We report two cases of PACNS with peculiar and atypical features: the first one with a possible Epstein Barr Virus (EBV) relationship, the second one with spinal cord involvement only, treated surgically. We also hypothesize a correlation between EBV chronic infection and possible subtypes of PACNS stressing the importance of EBER (EBV-encoded RNA) test in the routine examination of brain biopsies suspicious for PACNS.